Large-to Local-Scale Control of Pre-Existing Structures on Continental Rifting: Examples From the Main Ethiopian Rift, East Africa - Corti, Giacomo; Maestrelli, Daniele; Sani, Federico (Frontiers in Earth Science, 2022)
In the Main Ethiopian Rift (East Africa) a complex tectonic history preceded Tertiary rifting creating pre-existing discontinuities that influenced extension-related deformation. Therefore, this area offers the opportunity to analyze the control exerted by pre-existing structures on continental rifting at different scales. In this paper we present an overview of such an influence. We show that at a large scale (up to ~800-1000 km) rift localization has been controlled by a lithospheric-scale inherited heterogeneity corresponding to a Precambrian suture zone, separating two different lithospheric domains beneath the plateaus surrounding the rift. The inherited rheological differences between these two lithospheric domains, as well as the presence of pre-existing lithospheric-scale transversal structures, largely controlled the along-axis segmentation and symmetry/asymmetry of different, ~80-100 km-long rift segments. Inherited transversal structures also controlled the development of off-axis volcano tectonic activity in the plateaus surrounding the rift. At a more local scale (<80 km), inherited fabrics controlled the geometry of normal faults and the distribution and characteristics of rift-related volcanism. These observations document a strong control exerted by pre-existing structures on continental rifting at all different scales.